DAMPAK KENAlKAN BARGA MINYAK GORENG TERHADAP KELAYAKAN USAHA INDUSTRI RUMAH TANGGA KERIPIK TEMPE DI KECAMATAN RAWALO KABUPATEN BANYUMAS - Altri Mulyani; Masyhuri Masyhuri; Ken Suratiyah (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2008)
The objectives are to know: (1) the impact of cooking oil price increasing to the feasibility of tempe chips home industry; (2) income decreasing of tempe chips home industry after cooking oil price increasing; (3)factors affecting the profit of tempe chips home industry; (4) strategy of the tempe chips home industry when the production cost increase as cooking oil price increase. The research area is Rawalo sub-district, Banyumas district. Data collected by census method of 49 tempe home industries. Analyses used are RIC ratio, 1C/Cratio, BEP production, BEP revenue, BEP price, and Unit-Output-Price Cobb-Douglas Profit Function. The results show that: (1) tempe chips home industries have to be maintained although cooking oil price increasing has increased the product's price also; (2) after cooking oil price increasing period, tempe chips home industry has decreasing income; (3) UOP Cobb-Douglas Profit Function shows that cooking oil price, soybean price, cassava powder price, production capacity, dummy variable of before and after increasing cooking oil price period affect the profit function of tempe chips home industry; (4) strategy have been practiced by tempe chips home industries tempe chips product's size, decrease the tempe chips per pack capacity, decrease the production capacity, decrease the production frequency, and add cassava in the processing of tempe making.